A Dyadic Model of Stress, Coping, and Marital Satisfaction Among Parents of Children With Autism. Issue 1 (2nd August 2019) - Brown, Matthew; Whiting, Jason; Kahumoku‐Fessler, Emily; Witting, Alyssa Banford; Jensen, Jakob
Abstract : Objective: To investigate the relationships among dyadic coping, marital satisfaction, and parenting stress in the context of caring for a child with an autism spectrum disorder (ASD). Background: Extant literature demonstrates the negative effects of parenting stress on individual and couple functioning for parents of children with ASD. Yet little is known about how these couples utilize their couple relationship as a resource for coping with this stress (i.e., dyadic coping) and its impact on both marital satisfaction and parenting stress. Method: Data from a convenience sample of 69 married couples raising children with ASD were used to conduct analyses using the actor–partner interdependence model. Participants completed an online survey with measures of dyadic coping, marital satisfaction, and parenting stress. Path analysis models were used to test for the mediating effect of marital satisfaction on the relationship between dyadic coping and parenting stress. Results: Results showed that dyadic coping was positively associated with marital satisfaction and negatively associated with parenting stress. Marital satisfaction was also negatively associated with parenting stress, and several associations between dyadic coping and parenting stress were mediated by marital satisfaction. Conclusion: Findings suggest that dyadic coping holds important implications for the marital satisfaction and parenting stress of couples raising children with ASD. Implications: Those who work with parents of children with ASD should help couples develop relationship‐based coping strategies to reduce parenting stress.